2013
DOI: 10.2172/1097335
|View full text |Cite
|
Sign up to set email alerts
|

Initial Assessment of U.S. Refineries for Purposes of Potential Bio-Based Oil Insertions

Abstract: SUMMARYIn order to meet U.S. biofuel objectives over the coming decade the conversion of a broad range of biomass feedstocks, using diverse processing options, will be required. Further, the production of both gasoline and diesel biofuels will employ biomass conversion methods that produce wide boiling range intermediate oils requiring treatment similar to conventional refining processes (i.e. fluid catalytic cracking, hydrocracking, and hydrotreating). As such, it is widely recognized that leveraging existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 12 publications
(15 reference statements)
1
51
0
Order By: Relevance
“…A recent review by PNNL describes the US refineries that could be well suited to ‘biorefinery integration’, based on configuration . It was apparent that two characteristics are important in a refinery integrated with biobased intermediates, namely processes that convert large molecules into smaller molecules (cracking, with or without hydrogen) and processes that remove oxygen, primarily through hydrotreating.…”
Section: Potential Refinery Integration Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by PNNL describes the US refineries that could be well suited to ‘biorefinery integration’, based on configuration . It was apparent that two characteristics are important in a refinery integrated with biobased intermediates, namely processes that convert large molecules into smaller molecules (cracking, with or without hydrogen) and processes that remove oxygen, primarily through hydrotreating.…”
Section: Potential Refinery Integration Pointsmentioning
confidence: 99%
“…It was apparent that two characteristics are important in a refinery integrated with biobased intermediates, namely processes that convert large molecules into smaller molecules (cracking, with or without hydrogen) and processes that remove oxygen, primarily through hydrotreating. Earlier work has suggested that refineries that have no hydrotreating facilities are not suited for upgrading bio‐feedstocks unless oxygen removal is carried out prior to insertion …”
Section: Potential Refinery Integration Pointsmentioning
confidence: 99%
“…However, an alternative to this would be the transportation and subsequent upgrading of these bio-oils in a conventional petroleum refinery. As certain studies suggest, it would save a lot of capital investment and be economically feasible if the price of the bio-oil sold is comparable to crude petroleum prices [131].…”
Section: Life Cycle Assessment Of Thermochemical Technologies For Trementioning
confidence: 99%
“…Cracking is carried out with the aid of a catalyst, aerated by steam and acting as a liquid. Catalytic cracking refers to the most extensive processes in the developed countries of the world, such as the USA, Arab Emirates, Great Britain, and makes up to 35 % of the capacity of primary processing of crude oil [34].…”
Section: Co-processing Of Bio-oil With Petroleum Products In the Condmentioning
confidence: 99%
“…The co-processing in FCC blocks is a new and promising way of converting bio-oil into renewable gasoline and diesel fuel. Current studies are mainly aimed at revealing the potential of this technology and suggest that the coprocessing can provide significant potential for using the existing processing infrastructure for the processing of biomass, mainly lignocellulosic raw materials, and increase the supply of bio-oil to the market [34,35].…”
Section: Co-processing Of Bio-oil With Petroleum Products In the Condmentioning
confidence: 99%